Changes in Anti-nutritional Factors and Functional Properties of Extruded Composite Flour - Duguma, Haile Tesfaye; Forsido, Sirawdink Fikreyesus; Belachew, Tefera; Hensel, Oliver (Frontiers in Sustainable Food Systems, 2021)
Background: Development of complementary foods by mixing plant-based (cereals, pulses, oilseeds, and others) ingredients and employing various processing techniques is widely reported. However, information on comparison of anti-nutritional factors and functional properties of extruded and unextruded complementary flours made from a multi-mix is limited. In this regard, this study aims to investigate the influence of extrusion cooking on anti-nutritional and functional properties of newly developed extruded oats, soybean, linseed, and premix composite complementary flours. Methods: Thirteen different blending ratios of oats, soybean, linseed, and premix were generated using a constrained D-optimal design of the experiment. Each of the 13 blends was divided into two groups: extrusion cooked and unextruded composite flour sample. Anti-nutritional and functional properties were determined using standard methods for both composite flours. ANOVA was used to determine if there was a significant difference for extruded and unextruded composite flours and paired t-tests were used to check variation between extruded and unextruded. Results: The phytate content of the extruded and unextruded composite flours was 158.93–191.33 mg/100 g and 175.06–203.10 mg/100 g, respectively, whereas the tannin content of the extruded and unextruded composite flours was 8.4–22.89 mg/100 g and 23.67–36.97 mg/100 g, respectively. There was a statistically significant (p < 0.05) difference among the extruded composite flours in terms of phytate and condensed tannin content. Paired t-test has indicated a significant (p < 0.05) difference between extruded and unextruded composite flours for phytate and tannin. Water absorption capacity and bulk density have shown a significant (p < 0.05) difference among extruded and unextruded composite flours. An increase in the proportion of soybean and linseed flour was associated with an increase in phytate, tannin, and water absorption capacity of composite flours. However, bulk density was increased with an increasing proportion of oat in the blend. Conclusion: The findings revealed that extrusion cooking significantly reduced phytate and condensed tannin content and improved the functional properties of the composite complementary food flour. Further investigation is needed on other anti-nutritional factors that are not included in this report.